Material Designing in Language Teaching - Khodjieva Ranokhon Akmalovna (Genius Journals, 2021)
This article considers about material designing in language teaching. Also analyses types of teaching and learning materials. There are given some instructions for language teachers in developing materials for any aspect of language learning.
Keywords: Material Designing; Language Teaching; Instructions for Teachers; Developing Materials